2015
DOI: 10.1007/s10916-014-0182-2
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Studies on Usability of mHealth Apps: A Systematic Literature Review

Abstract: The release of smartphones and tablets, which offer more advanced communication and computing capabilities, has led to the strong emergence of mHealth on the market. mHealth systems are being used to improve patients' lives and their health, in addition to facilitating communication between doctors and patients. Researchers are now proposing mHealth applications for many health conditions such as dementia, autism, dysarthria, Parkinson's disease, and so on. Usability becomes a key factor in the adoption of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
402
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 577 publications
(420 citation statements)
references
References 72 publications
13
402
1
4
Order By: Relevance
“…Data gathered and disseminated through these means can be used to augment diagnosis and monitoring processes [7]. In addition to their use in physical conditions [8], mHealth may also be applied to the management of cognitive health [9]. However, although research examining the use of various health-related apps by older adults is helping to indicate what factors affect the use of such apps by this population [2,[8][9][10], there is a paucity of research investigating the use of touch screen tablets in assessing information or cognitive processing in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Data gathered and disseminated through these means can be used to augment diagnosis and monitoring processes [7]. In addition to their use in physical conditions [8], mHealth may also be applied to the management of cognitive health [9]. However, although research examining the use of various health-related apps by older adults is helping to indicate what factors affect the use of such apps by this population [2,[8][9][10], there is a paucity of research investigating the use of touch screen tablets in assessing information or cognitive processing in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluations of the usability of websites have been the subject of numerous research projects, with researchers focusing on topics such as e-learning (e.g., [10,11]), e-government (e.g., [12,13]), ecommerce (e.g., [14][15][16][17][18]), mobile website interfaces (e.g., [19,20]), m-commerce (e.g., [21,22]), and virtual and augmented reality (e.g., [23,24]). …”
Section: Literature Reviewmentioning
confidence: 99%
“…Matthew-Maich et al [65] have produced a scoping review investigating mobile health technologies for managing chronic conditions in older adults: they reported that most applications target specific conditions, are designed primarily for use by patients and care providers, and that evidence-based guidance on how to ensure acceptability and usability of mHealth innovations continues to be limited. Zapata et al [66] also explored mobile health technologies through a systematic review to investigate usability evaluation processes. They highlighted the importance of usability for adoption and use of mHealth by patients, many of them having limited experience and/or problems using mobile applications.…”
Section: Technology Human Factors and Usability: Old And New Problemsmentioning
confidence: 99%